Biocatalytic Chromium(VI) reduction by bacterial culture grown in symbiotic autotrophy with fresh water microalgae - Chirwa, Evans M.N. (University of Pretoria, 2019)
Dissertation ((MEng)Chemical Engineering)--University of Pretoria, 2019